2002
DOI: 10.1590/s1413-77392002000100001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and biomass of Chaetognaths off São Sebastião region, Brazil in February 1994

Abstract: (Praça do Oceanográfico, SP, Brasil) lavega@usp.br• Abstract: The distribution, abundance, biomass, population structure and feeding habits of chaetognaths collected off São Sebastião region, Brazil, in February 1994 are described. Bongo nets were hauled obliquely to collect zooplankton samples. Forty-three samples obtained with the 333 urn mesh were analysed. In this study, 7 chaetognath species belonging to two genera were identified. Sagitta friderici, S. tenuis and S. bipunctata were grouped into the ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…According to Marazzo and Nogueira (1996), it is typical of surface waters and specially abundant at the continental shelf where salinity ranges from 35 to 36. Liang and Vega-Pérez (2001) found low densities of F. enflata in the coastal region off Vitória, and observed that this species seemed to be limited to the areas of high salinity values (>36 PSU) found in the tropical waters of the region, since this is a semi-neritic species (Liang and Vega-Pérez 2002).…”
Section: Specific Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Marazzo and Nogueira (1996), it is typical of surface waters and specially abundant at the continental shelf where salinity ranges from 35 to 36. Liang and Vega-Pérez (2001) found low densities of F. enflata in the coastal region off Vitória, and observed that this species seemed to be limited to the areas of high salinity values (>36 PSU) found in the tropical waters of the region, since this is a semi-neritic species (Liang and Vega-Pérez 2002).…”
Section: Specific Compositionmentioning
confidence: 99%
“…Thirty-nine species have been reported in the South Atlantic so far, between 0 and 60°S (Boltovskoy 2005). Studies on chaetognaths in southeastern Brazil have concentrated on coastal and oceanic waters where these organisms are abundant (Almeida Prado 1968, Vega-Pérez and Liang 1992, Marazzo and Nogueira 1996, Liang and Vega-Pérez 2001, 2002, Vega-Pérez and Schinke 2011. However, chaetognaths can also be found in Brazilian estuaries, as reported by Lansac Tôha and Lima (1993) in the estuary of the Una do Prelado river, by Lira and Magalhães (1996) in the Mandaú/ Manguaba system in Alagoas, by Lopes (1996) in the estuaries of the Juréia-Itatins ecological station, by Montú (1980) in the Patos Lagoon estuary in Rio Grande and by Paranaguá and NascimentoVieira (1984) in the Botafogo river estuary.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, chaetognath studies have dealt mainly with distribution (Almeida Prado 1961a, Fernandes et al 2005 or population structure and feeding (Nair and Sankarankutty 1988, Vega-Pérez and Liang 1992, Liang and Vega-Pérez 1994, 1995, 2002. In Guanabara Bay, three species of chaetognaths are abundant; Parasagitta friderici Ritter-Zàhony is the dominant species, followed by Flaccisagitta enflata Grassi and Ferosagitta hispida Conant (Marazzo and Nogueira 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre esses destacam-se: "Nave Liguria" (Baldasseroni, 1915), "Meteor" (Thiel 1938) e "Terra Nova" (Burfield 1930). Posteriormente, outros trabalhos foram realizados por Vanucci & Hosoe (1952), Hosoe (1956), Alvariño (1980), Gusmão (1986), Nair & Sankarankutti (1988), Liang (1998) Almeida-Prado (1960, 1961a,b, 1963, Costa (1970Costa ( , 1971, Coelho (1993), Liang (1993), Liang & Vega-Pérez (2002), Resgalla & Montú (1995), Marazzo-Nogueira et al (1996), Vega-Pérez & Liang (1999), Liang et al (2003) e Vega-Pérez & Schinke (2008), estudaram a ocorrência e distribuição das que ocorrem nas regiões sudeste e sul. Aspectos relacionados aos hábitos alimentares dos quetógnatos foram abordados por Almeida-Prado (1968), Vega-Pérez & Liang (1992, Liang & Vega-Pérez (1995) e Marazzo et al (1997).…”
Section: Introductionunclassified